Cohort Study of the Incidence of Extrapancreatic Neoplasm During Clinical and Radiological Surveillance of Patients with Branch-Duct IPMN - Borin, Alex; Malleo, Giuseppe; Marchegiani, Giovanni; Accordini, Federico; Marchese, Tiziana; Butturini, Giovanni; Bassi, Claudio; Salvia, Roberto (JOP. Journal of the Pancreas, 2013)
Context In the latest years, there has been controversy about the relationship between intraductal papillary mucinous neoplasms (IPMN) and the development of extrapancreatic neoplasms. While a number of prevalence studies confirmed this association, the only cohort studies available did not. Objective This is a cohort study of patients with branch-duct IPMN and without a personal history of other non-pancreatic neoplasms who were enrolled in a radiological surveillance protocol. The objective was to assess the incidence of extrapancreatic neoplasms during the follow-up period in comparison with that of the Italian general population. Methods Patients with well-documented branch-duct IPMN on cross-sectional imaging (MRI) and devoid of malignancy concern (according to an institutional protocol from 2000 until 2005 and to the IAP guidelines from 2005 and onwards) were enrolled in a radiological surveillance protocol on a yearly basis. The occurrence of other non-pancreatic neoplasms was recorded in a prospective database and the incidence was compared with the Italian tumor registry (AIRTUM). In particular, number of expected cases was calculated, and the standardized incidence ratio (observed/expected cases) with 95% CI was obtained. Risk function for the development of extrapancreatic neoplasms was then plotted according to the method of Kaplan and Meier. For the purposes of this study, follow-up was stopped on July 2013. Results Study population consisted of 472 patients observed over a 12-year period (2000-2012). Median follow-up was 44 months. Fifty-nine patients (12.5%) developed at least an extrapancreatic malignant neoplasm, for a total of 61 neoplastic events. Median time-to-presentation was 34 months. The most frequent neoplasms were breast cancer (n=15), renal clear cell carcinoma (n=7), colorectal cancer (n=5), melanoma (n=5), lung cancer (n=5), prostate cancer (n=4), and thyroid cancer (n=4). The cumulate incidence of extrapancreatic neoplasms in the study population was significantly greater than the expected incidence in the Italian population, with a standardized incidence ratio of 1.75 (95% CI: 1.33-2.26). According to the plotted risk function, the risk of developing a non-pancreatic neoplasm increased over time (1 year: 2%; 2 years: 4%; 5 years: 8%). Conclusion Patients with branch-duct IPMN have a 1.75 fold increase of non-pancreatic neoplasms during the follow-up period. This warrants sub-analyses by sex, age, type of neoplasm, and possible revision of follow-up protocols, with targeted tumor screening.